Isolated Interrupted Aortic Arch- A Complex Congenital heart disease - Shariar, A; Huq, MA; Zakia, NU; Salim, M; Islam, SA (Cardiovascular Journal, 2012)
Interrupted Aortic Arch (lAA) is the absence or discontinuation of a portion of the aortic arch. There are three types of Interrupted Aortic Arch,and they are classified according to the site of the interruption. lsolated IAA appears commonly in type B lAA,where the interruption occurs between the left carotid artery and the left subclavian artery.In such case there is no associated cardiac anomaly and the patient may not exhibit lethal form of presentation unless there is duct dependent circulation or ventricular septal defect. lsolated interrupted arch is relatively rare congenital anomaly and very few cases were reported in literature so far. Keywords: lnterrupted aortic arch; Complex congenital heart disease. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9400 Cardiovasc. J. 2011; 4(1): 102-104